Growth of children 0-6 years of age in bushehr - Roozbeh F. (Iran University of Medical Sciences, 1999)
Background: Normal growth of children is basic index for their lealth. Assessing children's growth could help us to recognize those at risk or suffering from malnutrition. Objective: To determine the growth of 0-6 years old children of native families in Bushehr compared with standard. Design: This was a Cross-sectional study. According to weight and height using waterlow method the grade of malnutrition was described for all age groups. Sample: Seven hundred and twenty children reffered to clinics during research time were selected randomly (360boys;360girls). Result: All groups of children were below the average standard. Malnutrition were more sever in boys.By growing older the malnutrion became worse. Conclusion: More attention should be given to children's nutritional requirments specially when they are weaned off from breast feeding. Furthur research should be carried out in other cities of Iran.